Assessing virtual reality presence through physiological measures: a comprehensive review - Danping Wang; Danping Wang; Yunchao Peng; Yunchao Peng; Lise Haddouk; Lise Haddouk; Nicolas Vayatis; Nicolas Vayatis; Pierre-Paul Vidal; Pierre-Paul Vidal; Pierre-Paul Vidal; Pierre-Paul Vidal (Frontiers in Virtual Reality)
This review analyzes 94 articles in an attempt to define the concept of presence in virtual reality (VR). Two types of data were examined: physiological variables and questionnaires, which were used in 85% study of the selected articles. The physiological measurements focused mainly on head movements, as well as electromyographic and electrocardiographic activity. Over time, a gradual decrease in the use of questionnaires is noted, with a growing preference for physiological markers to define presence in VR. We analyzed papers with physiological measurement methods and noted additional usage of subjective questionnaires. This approach captures the complexity of the subject’s experience, which includes cognitive, emotional, and physical responses. Additionally, the increasing use of artificial intelligence, particularly deep learning, is a promising trend for defining this concept. Finally, this review raises two important issues that require further investigation. Firstly, the very nature of the neurophysiological variables recorded to detect presence: they are also recommended for quantifying stress and mental load, to name but a few behavioral characteristics. Consequently, none of them can be considered specific to presence in VR. Second, the number of people tested is often small, which often poses a problem, given the wide variety of methodologies used and the physiological and psychological reactions of the people tested in VR in the 94 studies we analyzed. Clearly, there is a need for larger-scale prospective studies to better define the concept of presence during a virtual reality immersion experience.